Multicenter Randomized Clinical Trial of Brief Psychotherapy versus Usual Treatment for Common Mental Disorders in Adults - Marco A. Luengo-Castro; Javier Fernández-Méndez; José M. García-Montes; Pedro J. Caunedo-Riesco; Juan M. García-Haro; Begoña Braña-Menéndez; Dolores González-Díaz; Andrés Cabero-Álvarez; Marcelino Cuesta-Izquierdo (Clínica y Salud. Investigación Empírica en Psicología)

(untitled)
Background: This paper addresses the evaluation of the effectiveness of brief psychological treatment (BPT) for common mental disorders (CMD) in mental health centers (MHC), comparing it to treatment as usual (TAU). Method: 144 patients were randomly assigned to either the experimental treatment group (EG), receiving BPT, or the control group (CG), receiving TAU. Pre-treatment and up to 3-year assessments were conducted on clinical-administrative, symptomatic, disability, satisfaction, and psychopharmacological consumption. Results: The EG had an average of 7 sessions compared to 6.17 sessions for the CG. At 6 months, the CG – with 70% exclusively receiving psychopharmacological treatment – showed better symptomatic improvement than the EG, but worsened after one year. The EG initially exhibited a more modest improvement pattern, but continued and became more effective than TAU after one year. Conclusions: In the medium term, BPT proves to be more effective with longer-lasting effects.